Synergistic effects of Gefitinib and Paclitaxel in breast cancer treatment using cockle shell-derived nanoparticle - Chemmalar, Sangaran (2023)
Breast cancer is the most common type of cancer in women worldwide, including in Malaysia, ranking second in terms of mortality rate. The problem with conventional chemotherapy and radiotherapy is that they also elicit adverse effects on healthy cells. Nowadays, nanoparticle-based drug carriers and targeted therapies are used as alternative treatments since they demonstrate improved efficacy and safety. Nanoparticle based drug carriers can carry and deliver multiple drugs at the tumor site due to the leaky tumor vasculature. Epidermal growth factor receptor (EGFR) overexpression has been correlated with poor prognosis in many breast cancer patients. Gefitinib (GEF), an EGFR-Tyrosine kinase inhibitor, must be administered orally, and it leads to adverse skin reactions and gastrointestinal problems. Paclitaxel (PTXL), an antimitotic drug, is poorly water-soluble, and needs to be administered with a solvent, which leads to hypersensitivity and neuropathies in some patients. Further, GEF and PTXL have synergistic properties. Calcium carbonate as a nanoparticle has gained popularity due to its inherent properties such as biocompatibility, pH-sensitivity, and slow biodegradability. Hence, this Ph.D. work focuses on developing three types of drug-loaded calcium carbonate nanoparticles (CSCaCO3NP) utilizing the blood cockle shell (Anadara granosa) waste, resulting in GEF-CSCaCO3NP, PTXL-CSCaCO3NP, and dual drug-loaded GEF-PTXL-CSCaCO3NP. Subsequently, the aim was to determine the physicochemical and biological characteristics of the synthesized nanoparticles in MCF-7 and SK-BR-3 cell lines. The results reveal that the CSCaCO3NP, GEF-CSCaCO3NP, PTXL-CSCaCO3NP, and GEF-PTXL-CSCaCO3NP were almost spherical with a diameter of 63.9 ± 22.3, 83.9 ± 28.2, 78.2 ± 26.4, and 87.2 ± 26.7(nm), respectively, and were negatively charged, aragonite and mesoporous, with a surface area ranging from ⁓8 to 10(m2/g). CSCaCO3NP shows excellent alkalinization properties in plasma simulating conditions and greater solubility in a moderately acidic pH medium (pH 5.6). The nanoparticles showed zero-order drug kinetics, with a slow and sustained release even up to 100 hours. The biocompatibility study with Human Mammary Epithelial cells (HMEC) revealed that the nanoparticles were nontoxic. The relationship between the drugs was determined using XTT and Resazurin reduction assays and it showed synergism. Colonigenic assay against MCF-7 and SK-BR-3 cell lines resulted in 0% colonies after treatment with PTXL-CSCaCO3NP, and GEF-PTXL-CSCaCO3NP, whereas at IC50 concentrations, GEF-CSCaCO3NP treated group had persisting colonies. Electron microscopic examinations showed that the MCF-7 cells had undergone apoptotic changes and showed characteristic changes like autophagosomes and thicker microfilament bundles, respectively, for GEF-CSCaCO3NP and PTXL-CSCaCO3NP treatments, which were concurrent with the beta tubulin stabilization in MCF-7 and SK-BR-3 cells, as detected using immunofluorescence. Final investigations revealed that GEF-PTXL-CSCaCO3NP was very effective in up-regulating the apoptotic markers Caspase-3 and BAX in the MCF-7 cell line. GEF-PTXL-CSCaCO3NP against MCF-7 showed synergistic inhibition of EGFR2 at Y1248, similar to EGFR at Y1173. In contrast, only the pure drug GEF had lower levels of p-Tyr1068 of EGFR, whereas the drug-loaded nanoparticles had lower inhibition of phosphorylation. In conclusion, the properties of GEF-CSCaCO3NP, PTXL-CSCaCO3NP, and GEF-PTXL-CSCaCO3NP prove that they deliver the payload, and GEF-PTXL-CSCaCO3NP has a high potential, possessing synergistic characteristics that will be a boost in certain breast cancer management.